Subsistence Whaling
VII, 168 p. 13 illus., 9 illus. in color.
Keywords: This book examines the past history, and contemporary status of subsistence whaling. The papers derive from a symposium ‘Aboriginal Whaling and Identity in the 21st Century’ held at the Eleventh Conference on Hunting and Gathering Societies in Vienna, Austria in September 2015. Whales, especially large baleen whales, are the largest animals targeted by many societies, prehistoric or modern, and major facets of subsistence, social structure and ideology are still deeply embedded in past and current whaling lifeways. Yet there is probably no other environmental/political issue that has attracted as much attention in the late 20th and early 21st century as whaling practices and policies. Accordingly, the papers address two major themes: 1) the extent and characteristics of major prehistoric and early historic whaling activities, and 2) case studies amongst modern whaling societies, and how these societies are impacted by current political and economic realities and by the anti-whaling movement.